Does agricultural mechanization improve agricultural environmental efficiency? - Yan, Fuzhen; Sun, Xuetao; Chen, Suisui; Dai, Guilin (Frontiers in Environmental Science, 2024)
Improving agricultural environmental efficiency (AEE) is critical for sustainable and green agricultural advancement. However, there is limited research on the impact of agricultural mechanization on agricultural environmental efficiency. This study innovatively used micro-level survey data from the national fixed observation points of China's Ministry of Agriculture and Rural Affairs to employ a super-efficiency slacks-based measure (SBM) model with undesirable outputs for quantifying AEE. Additionally, a Tobit regression model was used to examine the influence of agricultural mechanization on AEE. Our findings revealed a 'U-shaped' relationship between agricultural mechanization and AEE. Specifically, when the extent of mechanization fell below a particular threshold, any further increase adversely affected the AEE. Conversely, surpassing this threshold enhanced the AEE. This 'U-shaped' effect was mediated by agricultural carbon emissions. Furthermore, our analysis indicated that relative to other village categories, the benefits of mechanization in elevating AEE are more pronounced in plain, agriculturally focused, and affluent villages. To promote the improvement of agricultural environmental efficiency, it is advisable to advance agricultural mechanization, reduce agricultural carbon emissions, and develop agricultural mechanization tailored to local conditions.